1986
DOI: 10.2337/diab.35.3.341
|View full text |Cite
|
Sign up to set email alerts
|

Renin Secretion by the Spontaneously Diabetic Rat

Abstract: Renal function studies and measurements of in vivo plasma renin activity (PRA), kidney renin content, and renin secretion by isolated, perfused kidneys were performed in spontaneously diabetic and nondiabetic BioBreeding/Worcester (BB/W) rats. Diabetic animals evidenced hyperglycemia, glycosuria, and plasma volume expansion. After dietary sodium deprivation, plasma volume fell to levels equivalent to those of sodium-deprived, nondiabetic rats. Dietary sodium deprivation evoked a larger proportional increase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
1

Year Published

1987
1987
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 18 publications
2
10
1
Order By: Relevance
“…Interestingly, the increase of ΔHR/ΔMABP, an indicator of BRS, was greater in DM rats compared with Ctr rats in response to PE and SNP injections. This result is not consistent with those of some DM models, which may be largely attributed to the different time course of development for diabetes (ie, 12, 24, and 48 weeks): metabolic disorders caused by a hyperglycemic state or insulinopenia may be related to time-dependent changes in parasympathetic and sympathetic control [25,26] and different osmotic diuresis after the DM model was established [27,28] . In addition, discrepancies in species, experimental design and diabetic inducer may also affect the results to some extent [29,30] .…”
Section: Discussioncontrasting
confidence: 50%
“…Interestingly, the increase of ΔHR/ΔMABP, an indicator of BRS, was greater in DM rats compared with Ctr rats in response to PE and SNP injections. This result is not consistent with those of some DM models, which may be largely attributed to the different time course of development for diabetes (ie, 12, 24, and 48 weeks): metabolic disorders caused by a hyperglycemic state or insulinopenia may be related to time-dependent changes in parasympathetic and sympathetic control [25,26] and different osmotic diuresis after the DM model was established [27,28] . In addition, discrepancies in species, experimental design and diabetic inducer may also affect the results to some extent [29,30] .…”
Section: Discussioncontrasting
confidence: 50%
“…Jackson and Carrier (16) suggested that the decrease in AP may be the result of a decreased cardiac output in diabetic sedentary rats due to hypovolemia caused by hyperglycemic osmotic diuresis. However, Cohen et al (17) observed that these animals were polyuric with a high urine flow, reflecting the osmotic diuretic effects of glucose. The hypotension observed in the sedentary diabetic group may also have been due to an increase in parasympathetic outflow, although Maeda et al (2) and the present data demonstrated a decrease in vagal function, suggesting that changes in AP are not related to an increase in parasympathetic outflow.…”
Section: Discussionmentioning
confidence: 99%
“…Jackson and Carrier (1) suggested that the decrease in AP may be the result of a decreased cardiac output in diabetic rats due to hypovolemia caused by hyperglycemic osmotic diuresis. However, Cohen et al (13) observed that the diabetic animals were polyuric with a high urine flow, reflecting the osmotic diuretic effect of glucose. In these experiments, the renal physiologic parameters demonstrated increased plasma volume, presumably related to osmotic effects of glucose resulting in both expansion of extracellular fluid volume and induction of diuresis (13).…”
Section: Introductionmentioning
confidence: 99%
“…However, Cohen et al (13) observed that the diabetic animals were polyuric with a high urine flow, reflecting the osmotic diuretic effect of glucose. In these experiments, the renal physiologic parameters demonstrated increased plasma volume, presumably related to osmotic effects of glucose resulting in both expansion of extracellular fluid volume and induction of diuresis (13). In the present study, the collection of blood samples may have contributed to the changes in AP, although the rats were injected with equal volumes of saline after collection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation